2013
DOI: 10.12816/0000053
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Gingivitis in Pregnancy : A Comparative Study between First and Third Trimesters of Pregnancy

Abstract: Objective: The aims of this study were to determine the incidence of gestational gingivitis and assess oral health status in two groups of women at different stages of pregnancy. Methods: A comparative descriptive study was conducted on pregnant women attending the outpatient antenatal care clinic at Princess Haya Hospital in Aqaba from January 2010 to August 2010. Data were collected from 580 women. Two groups were created. The first group (n=260) included women at their first trimester and the second group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
(23 reference statements)
2
5
0
Order By: Relevance
“…The prevalence of periodontal disease tends to increase with gestational age. [ 19 20 ] The result in this study was similar to those of previous studies,[ 19 20 ] but in contrast to some other studies. [ 4 8 ] The finding in this study may be explained by the fact that progesterone and estrogen increases with gestational age of pregnancy reaching their peak plasma levels of 100 ng/ml and 6 ng/ml, respectively, in the third-trimester.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The prevalence of periodontal disease tends to increase with gestational age. [ 19 20 ] The result in this study was similar to those of previous studies,[ 19 20 ] but in contrast to some other studies. [ 4 8 ] The finding in this study may be explained by the fact that progesterone and estrogen increases with gestational age of pregnancy reaching their peak plasma levels of 100 ng/ml and 6 ng/ml, respectively, in the third-trimester.…”
Section: Discussionsupporting
confidence: 91%
“…[ 3 21 ] The plausible reasons may be attributed to negligence of oral hygiene and intolerance early in pregnancy, which they were able to overcome as the gestational age increased. [ 19 22 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published literature have shown that the prevalence rates of gingivitis during pregnancy range between 30% and 100 %. (14,15) The prevalence of gingivitis in pregnancy was reported 85.2% in Nigerian population (16) and 86.2% in Thailand population (11) . The variability in findings can be attributed to genetic, hormonal and oral hygiene habit variation.…”
Section: Discussionmentioning
confidence: 99%
“…The fact the all the participants were brushing their teeth may be due the fact that we included in our study only pregnant females with adequate oral hygiene. Al-Rayyan et al (16) researched on large sample of pregnant females (n=580) in Jordon population and reported that most common pattern of brushing was less effective. The variation can be attributed to sample size difference and awareness among participants.…”
Section: Discussionmentioning
confidence: 99%